Quantitative hemodynamics of draining veins in brain arteriovenous malformation: a preliminary study based on computational fluid dynamics - Ma, Long; Chen, Yu; Chen, Pingting; Ma, Li; Yan, Debin; Li, Ruinan; Li, Zhipeng; Zhang, Haibin; Han, Heze; Yuan, Kexin; Li, Runting; Lin, Fa; et al. (Frontiers in Neurology, 2024)
ObjectiveThis study initiated a preliminary computational fluid dynamics (CFD)-based study to investigate the relationship between quantitative hemodynamics of arteriovenous malformation (AVM) draining veins and rupture.MethodsThe quantitative hemodynamics of AVM draining veins were generated from computed tomography angiography (CTA)-based steady-state CFD models. Morphological and hemodynamic parameters were compared between the ruptured and unruptured groups. The boundary conditions of the drainage vein were obtained from quantitative digital subtraction angiography (QDSA). The draining veins were divided into 15 consecutive segments to analyze the spatial distribution of the hemodynamic parameters by linear regression analysis.ResultsFrom 11 AVMs, it was revealed that morphological parameters of drainage veins in ruptured and unruptured AVMs were similar. The intravascular pressure of the draining vein in the ruptured AVMs was significantly higher than those of the unruptured AVMs (pressure average: p = 0.006; pressure maximum: p = 0.045), and the WSS of the posterior segment was higher in ruptured AVMs (p = 0.045). WSS of draining veins in ruptured AVMs showed a linear increase trend with segmenting (R = 0.731, p < 0.001), and ruptured AVMs were more likely to be accompanied by high-velocity segments in the draining vein (40.0% vs. 14.7%, p = 0.037), especially in the posterior segment (p = 0.011).ConclusionThe draining veins of ruptured AVMs had significantly higher intravascular pressure and posterior segment WSS. WSS showed a linear increase with segmentation in ruptured AVMs, and they often had more high-velocity segments in the draining vein, especially in the posterior segment.